PERBEDAAN HARGA SAHAM SEBELUM DAN SESUDAH PENGUMUMAN STOCK SPLIT PADA PERUSAHAAN YANG LISTING DI BURSA EFEK INDONESIA PERIODE 2008-2013 - Indra Saputra (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2017)
Abstract,The purpose of this research was to found whether there are differences in stock prices 7 days before and 7 days after the announcement of stock split within 33 company which registered in Indonesia Stock Echange in the period 2008-2013. The Method in this research is Paired Sample T-Test using SPSS version 16.00 for Window. The results of this research found difference between the stock price before and after the date of the announcement of stock split.The results can be see from the calculation of statistical test or t test that shows the value of t arithmetic to test the hypothesis of 3.670 with the results of the significance of 0.001 which is less than 5% or 0.05 so that we can conclude the hypothesis H1, which states that there are differences significantly between the share price before the announcement after the stock split and stock split is acceptable.